The veracity of prophecy and Christ's knowledge - Gaine, S (Wiley, 2016)
It is widely assumed by scholars that Christ was in error on such matters as an expectation that the final judgement and its accompanying events would occur within the timeframe of a generation. While accepting that Christ did indeed prophesy his return within this timeframe, a recent co‐authored work When the Son of Man Didn't Come aims to defend the veracity of his prophecy by drawing on the same historical‐critical method that has given rise to doubts about it. The authors propose a distinction between Mosaic and Jeremianic prophecy, arguing that Christ's was of the latter kind, which was present in the Ancient Near East, the Old and New Testaments, and other Jewish and Christian authors. Their argument, however, is at risk of reducing the truthfulness of a prophecy to its success. Hence this article explores a further distinction between two kinds of prophecy made in Thomas Aquinas's account of the truthfulness of prophecy, mapping it onto the Mosaic‐Jeremianic distinction, and arguing that, in view of this linking of Aquinas's understanding of prophecy to the argument of the book, the book certainly adds to the set of proposed theological explanations of how Christ's prophecy of his return was true.